1984
DOI: 10.1111/j.1365-2125.1984.tb02405.x
|View full text |Cite
|
Sign up to set email alerts
|

Temazepam's efficacy in patients with sleep onset insomnia.

Abstract: The hypnotic efficacy of temazepam capsules (30 mg) was studied in twelve patients who had objective polysomnographic evidence of sleep onset insomnia. Patients slept in the laboratory, retiring at their usual bedtime after taking placebo or temazepam 30 min earlier, and were monitored for 8 h using standard polysomnographic techniques. Acute (nights 5‐7) and chronic (nights 11‐13) temazepam improved the sleep of these patients by reducing sleep latency and increasing sleep time compared to the placebo baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The prevalence of rebound insomnia was found to be significantly lower in all benzodiazepines compared to triazolam [52,[60][61][62][63][64][65][66][67][68][69] and was lower than that with triazolam. Thus, similarly to rebound anxiety, the risk seems related to benzodiazepine elimination half-life and potency [20,23] and independent form the length of treatment [1].…”
Section: Rebound Symptoms After Benzodiazepine Discontinuationmentioning
confidence: 75%
“…The prevalence of rebound insomnia was found to be significantly lower in all benzodiazepines compared to triazolam [52,[60][61][62][63][64][65][66][67][68][69] and was lower than that with triazolam. Thus, similarly to rebound anxiety, the risk seems related to benzodiazepine elimination half-life and potency [20,23] and independent form the length of treatment [1].…”
Section: Rebound Symptoms After Benzodiazepine Discontinuationmentioning
confidence: 75%
“…Post-randomization, patients were required to visit the clinic at the end of weeks 1, 2, 4 and 6 and to return for follow-up visits 14 and 28 days after last dose. Efficacy and safety assessments conducted at each visit included the HAM-D (17-item using the SIGH-D, Williams, 1988), Clinical Global Impressions - Severity of Illness (CGI-S) and Improvement (CGI-I, Guy, 1976) (Guy, 1976), the Clinical Global Impression of Improvement (CGI-I, 18), the Quick Inventory of Depressive Symptomatology (self-reported, QIDS-SR, Rush et al, 2003), the Cognitive and Physical Function Questionnaire (CPFQ, Fava et al, 2009), the Morning Sleep Questionnaire (Roehrs et al, 1984, captured by Clinphone Plc, Nottingham, UK), the Columbia Suicidality Severity Rating Scale (CSSRS, Posner et al, 2011), and the Massachusetts General Hospital Sexual Functioning Questionnaire (MSFQ, Fava et al, 1998; Labbate and Lare, 2001). The Discontinuation-Emergent Signs and Symptoms (DESS, Fava, 2006) scale was administered at the end of double-blind treatment and the 14 day follow-up visit.…”
Section: Efficacy Studiesmentioning
confidence: 99%
“…Temazepam produced a number of improvements in the objective sleep of both osteoarthritic patients and controls. Several studies have reported a reduction in sleep latency following nocturnal temazepam administration (Beary et af., 1984;Roehrs et al, 1984). It is hardly surprising that temazepam did not reduce sleep latency in this study, since it was given only five min before bedtime.…”
Section: Discussionmentioning
confidence: 74%